iPod touch Made Simple - Trautschold, Martin; Mazo, Gary.; SpringerLink (Online service) (Berkeley, CA : Apress, 2010)
The iPod touch is much more than just music. You have all of the features of a PDA$1 (Bincluding email, calendar, Google Maps, the App Store, and even phone capabilities$1 (Bas well as the ability to watch movies and play your favorite games, all packed into Apple$1 (Bs sleek design. With iPod touch Made Simple, you'll learn how to take advantage of all these features and more. Packed with over 1,000 visuals and screenshots, this book will help you master the all of the functions of the iPod touch and teach you time-saving techniques and tips along the way. Written by two successful smartphone trainers and authors, this is the go-to guide for the iPod touch.s
Quick Start Guide -- Getting Around Quickly -- You and Your iPod touch -- Getting Started -- Typing Tips, Copy/Paste, and Search -- Sync Your iPod touch with iTunes -- Other Sync Methods -- Wi-Fi Connectivity -- Organize Your iPod touch Icons and Folders -- Personalize and Secure Your iPod touch -- Multitasking and Voice Control -- Playing Music -- Viewing Videos, TV Shows, and More -- iBooks and E-Books -- Surfing the Web with Safari -- FaceTime Video Messaging and Skype -- Email on Your iPod touch -- Working with Contacts -- Your Calendar -- iPod touch Photography -- Recording and Editing Videos -- iTunes on Your iPod touch -- The Amazing App Store -- Games and Fun -- Social Networking -- Eliminate Your Paper Notes -- Bluetooth on the iPod touch -- Utilities: Clock, Calculator, and Weather -- New Media: Reading Newspapers, Magazines, and More -- Find Your Way with Maps -- Troubleshooting -- iPod touch$1 (Bs Soulmate: iTunes -- Your iTunes User Guide.s
Keywords: Computer science; Computer Science; Computer Science, general